Advances in financial economics. Vol. 6 - Hirschey, Mark (Advances in financial economics., 2001)
On the existence of sub-standard security markets: the IPOs of blinder-robinson (J.S. Ang, S.L. Brown). Is managerial equity ownership an alternative governance mechanism for Japanese firms? (S.P. Ferris, K.A. Kim, P. Kitsabunnarat). The influence of managerial reputation on dividend smoothing (K.P. Fuller). Effects of harmful environmental events on reputation of firms (K. Jones, P.H. Rubin). Executive compensation and executive contributions to corporate PACS (K.A. Farrell, P.L. Hersch, J.M. Netter). The wealth effects of board composition and ownership structure in international acquisitions (S. Sundaram, I. Chhachii, S. Rosenstein). Corporate bankruptcy, private creditors, and the market for corporate control (M.B. Slovin, M.E. Sushka, E.R. Waller). The role of federal law enforcement actions in coroporate governance (M. Hirschey, E. Jones). Empirical evidence on determinants of capital structure (T. Jandik, A.K. Makhija).